An experimental investigations and optimization of performance measures in EDM using copper and graphite electrodes. (2021) - Selvarajan, L.; Rajavel, R.; Venkataramanan, K.; Elango, T.; Dhinagaran, M.
Abstract: In this research an experimental work were carried out on EDM of SS316 material using copper electrode and graphite electrode. Taguchi design have been analyzed the experiments of both electrodes using ANOVA. Analysis were done to investigate the effects of the process parameters viz. spark on time, spark off-time & current and constant IPOL dielectric fluid (C) were it effects on material removal rate, surface roughness and process parameters using Taguchi function approach of MINITAB software. As result shows that Comparing machining parameters of both electrodes the Graphite electrode is better than the copper electrode using SS316 material.